Internal Control System in Moderating the Understanding of Accounting and The Application of Accounting Information Systems on the Quality of Village Government Financial Statements in Deli Serdang District - Nasutio, Mardiah Hasanah; Martin, Martin (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
An understanding of accounting in budget absorption is needed where a budget must present a final report as accountability for budget realization. By building an accounting information system for absorption and reporting of regional budgets, it can be ensured that financial reports will find a level of reporting accuracy in presenting accountability. Facts in the field also show that the need for time in reporting can result in delays in the distribution of village funds phase II and III. The main cause is the incompleteness of the budget realization report or the achievement of the previous year's village fund output. In actualizing the Village Government Work Plan (RKPDes) and implementing the Village Budget (APBDes) based on the principles of accountability and transparency, the village head is less able to streamline teamwork (team building), lack of understanding of regulations and management policies. The data analysis technique used in this study used the Structure Equation Model (SEM) method based on Partial Least Square (PLS). The population in this study was 380 villages. The sampling technique used the Slovin method with an error rate of 5%, resulting in a research sample of 195 villages. accounting understanding directly has a significant effect on the quality of financial statements, the accounting information system directly has a significant effect on the quality of financial statements and the internal control system directly has no effect on the quality of financial statements of the Village government of Deli Serdang Regency. The results of variable moderation show that the accounting information system variable moderates the effect of accounting understanding and accounting information systems on the quality of financial statements in the Village Government of Deli Serdang Regency